2015
DOI: 10.1016/j.neubiorev.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A decade from discovery to therapy: Lingo-1, the dark horse in neurological and psychiatric disorders

Abstract: Leucine-rich repeat and immunoglobulin domain-containing protein (Lingo-1) is a potent negative regulator of neuron and oligodendrocyte survival, neurite extension, axon regeneration, oligodendrocyte differentiation, axonal myelination and functional recovery; all processes highly implicated in numerous brain-related functions. Although playing a major role in developmental brain functions, the potential application of Lingo-1 as a therapeutic target for the treatment of neurological disorders has so far been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 243 publications
(262 reference statements)
2
31
1
Order By: Relevance
“…These disease-linked channel and synapse-associated genes were largely down-regulated in the SCZ hGPCs, and included a number of potassium channel genes (Figure 4D), including KCND2, KCNJ9, KCNK9 and KCNA3, as well as a number of transcripts associated with synaptic development and function (Figure 4E and Table S2). The latter included NXPH1, NLGN3, and LINGO1, among others (Table S3, and Figures S3 and S4), synaptic genes whose dysregulation has been previously linked to both SCZ and the autism spectrum disorders (Andrews and Fernandez-Enright, 2015; Fernandez-Enright et al, 2014; Mackowiak et al, 2014; Salyakina et al, 2011; Sudhof, 2008). Whereas the expression of these latter genes was suppressed in hGPCs derived from all 4 SCZ patients, other synapse-associated genes, such as NRXN1, NLGN1, DSCAML1, and the SLITRKs 2–5, were sharply down-regulated in hGPCs derived from 3 of the 4 patients, but not in the fourth (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…These disease-linked channel and synapse-associated genes were largely down-regulated in the SCZ hGPCs, and included a number of potassium channel genes (Figure 4D), including KCND2, KCNJ9, KCNK9 and KCNA3, as well as a number of transcripts associated with synaptic development and function (Figure 4E and Table S2). The latter included NXPH1, NLGN3, and LINGO1, among others (Table S3, and Figures S3 and S4), synaptic genes whose dysregulation has been previously linked to both SCZ and the autism spectrum disorders (Andrews and Fernandez-Enright, 2015; Fernandez-Enright et al, 2014; Mackowiak et al, 2014; Salyakina et al, 2011; Sudhof, 2008). Whereas the expression of these latter genes was suppressed in hGPCs derived from all 4 SCZ patients, other synapse-associated genes, such as NRXN1, NLGN1, DSCAML1, and the SLITRKs 2–5, were sharply down-regulated in hGPCs derived from 3 of the 4 patients, but not in the fourth (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Activation and function of EGFR can either affect or be affected by other EGFR-interacting molecules in the CNS, such as mTOR and LINGO-1 (leucine-rich repeat and immunoglobulin domain-containing protein), which is evolutionarily related to LRIG-1 (14,43). EGFR signaling can activate mTOR in the CNS of adult animals, thereby promoting protein synthesis and axon regeneration after injury (43).…”
Section: Egfr and Cns Injury Recoverymentioning
confidence: 99%
“…It is ubiquitously expressed in the embryonic mouse before E7.5, but by E17.5 and later, it is expressed exclusively in the CNS with highest levels found within the neocortex, hippocampus, piriform cortex, and amygdala, corresponding to similar regions of EGFR expression (74). Studies have shown that LINGO-1 can directly bind to EGFR and inhibit its activation and/or reduce its expression, which is independent of EGF-mediated activation (14,235 …”
Section: Egfr and Cns Injury Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…LINGO-1 (leucine-rich repeat and Ig containing Nogo receptor interacting protein-1), also known as LERN1 and LRRN6A, is selectively expressed by oligodendrocytes and neurons in the central nervous system (CNS). [1][2][3][4] LINGO-1 expression regulates the timing of CNS myelination during development and LINGO-1 upregulation in neurological disorders suggests a deleterious role for the endogenous protein. 1,2,5,6 Blocking LINGO-1 function leads to robust remyelination in chemicaland immune-induced demyelination animal models.…”
Section: Introductionmentioning
confidence: 99%